2021
DOI: 10.1007/s11103-021-01150-y
|View full text |Cite
|
Sign up to set email alerts
|

An amino acid ester of menthol elicits defense responses in plants

Abstract: Terpenoids, including menthol, exhibit potent abilities as plant defense potentiators in agriculture and horticulture. In the current study, we developed new terpene derivatives that consisted of menthol and various amino acids and that were expected to act as powerful plant defense potentiators. We used 6 amino acids possessing low-reactive sidechains to synthesize an array of amino acid ester of menthol (ment-aa) compounds. Transcript levels of two defense genes (pathogenesis-related 1 [PR1] and trypsin inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(32 reference statements)
1
7
1
Order By: Relevance
“…Otherwise, the data shown with a p value are marginally different from those of Ct. reported for valine menthyl ester, a previously developed plant defense potentiator for crops, such as soybean, which was effective only at 1 μM. 14 It is possible that higher doses of REO may be harmful to plants and, thus, ineffective as a plant defense potentiator. For example, it has been shown that elevated levels of menthone from peppermint EO can disrupt microtubules and rapidly permeabilize the plasma membrane, leading to plant mortality.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, the data shown with a p value are marginally different from those of Ct. reported for valine menthyl ester, a previously developed plant defense potentiator for crops, such as soybean, which was effective only at 1 μM. 14 It is possible that higher doses of REO may be harmful to plants and, thus, ineffective as a plant defense potentiator. For example, it has been shown that elevated levels of menthone from peppermint EO can disrupt microtubules and rapidly permeabilize the plasma membrane, leading to plant mortality.…”
Section: ■ Discussionmentioning
confidence: 99%
“…10−13 In addition, our studies on the properties of peppermint VOCs, especially menthol, have led to the development of valine menthyl ester, a remarkably effective plant defense potentiator for soybean plants. 14 However, there is still a lack of sufficient examples that adequately address this important issue. Therefore, our research focused on investigating the efficacy of 11 different EOs in stimulating defense responses in tomato plants.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These AMTs might aid in delivering NH Organic compounds in the soil can also aid plant N nutrition (Geisseler et al, 2022). Amino acids account for the majority of low molecular weight dissolved organic N in soil (Tsuzuki et al, 2022). Evidence suggests that Arabidopsis has a single target of rapamycin (TOR) kinase gene (AtTORC) which is known to be involved in the maintenance of N metabolism including accumulation of amino acids thereby, influencing plant growth and metabolism (Caldana et al, 2013;Dobrenel et al, 2016).…”
Section: Gene Expression Action Referencesmentioning
confidence: 99%
“…Wound and UV-B-inducible patterns of their genes are consistent with the general defensive roles of flavonoids. Tsuzuki et al (2021) proposes the application of a menthol derivative, called ment-Val, that can boost the expression of defense genes to reduce pest damage in soybean plants and other crops. Their findings could usher in a change from harmful chemical pesticides to sustainable and environment-friendly alternatives.…”
mentioning
confidence: 99%